Association between esophagogastric varices in hepatocellular carcinoma and poor prognosis after transarterial chemoembolization: A propensity score matching analysis - Chien-Wei Su; Kuan-Chieh Fang; Rheun-Chuan Lee; Chien-An Liu; Ping-Hsien Chen; Pei-Chang Lee; Wei-Yu Kao; Yi-Hsiang Huang; Teh-Ia Huo; Ming-Chih Hou; Han-Chieh Lin; Jaw-Ching Wu (Journal of the Formosan Medical Association, 2020)
Background/Purpose: Whether esophagogastric varices (EGV) can determine the outcome of patients with hepatocellular carcinoma (HCC) after transarterial chemoembolization (TACE) remains unknown. This study aimed to assess the impact of EGV on the prognosis of HCC patients after TACE. Methods: From 2007 to 2012, we retrospectively enrolled 251 treatment-naïve HCC patients who underwent TACE and received esophagogastroduodenoscopy when HCC was diagnosed. The prognostic factors were analyzed using a Cox proportional hazards model and propensity score-matching analysis. Results: There were 120 (47.8%) patients with EGV. Compared to those without EGV, patients with EGV had worse liver functional reserve. After a median follow-up of 14.7 months (25th–75th percentiles, 6.4–35.6 months), 152 patients died. The cumulative 5-year overall survival (OS) rates were 11.2% and 38.8% in patients with and without EGV, respectively (p < 0.001). Multivariate analysis showed that presence of EGV, presence of ascites, tumor size >5 cm, serum alpha-fetoprotein >20 ng/mL, progressive disease by modified Response Evaluation Criteria in Solid Tumors, Assessment for Retreatment with TACE score ≥2.5, and higher albumin-bilirubin grades were the independent predictors of poor OS. Subgroup analysis also demonstrated that EGV was associated with poor OS in most of the subgroups. After propensity score matching, the EGV group still had a lower OS rate than their counterparts (p = 0.004). Conclusion: HCC patients with EGV had worse liver functional reserve compared to those without EGV. Moreover, EGV was an independent risk factor to predict poor prognosis in patients with HCC after TACE. Keywords: Hepatocellular carcinoma, Esophageal varices, Prognosis, Cirrhosis